The Role of Allied Health Technicians (Dental Assistants and Medical Device Technicians) in Enhancing Patient Safety in Healthcare Settings - Zuwayyid Almutairi, Abdullah Atallah; Saeed Alsirhani, Mohammed Turki; Nawar Almutairi, Adel Fehaid; Mislat Almarzuqi, Mazen Dabsan Bin; A Alghamdi, Faris Ibrahim; Ghadhban Aldhafeeri, Nawal Muhawish (Journal of Neonatal Surgery, 2025)
Introduction: The fast development of the Saudi Arabian healthcare industry in the framework of Vision 2030 has preconditioned the transition to multidisciplinary safety models. Although much research is done on clinicians, contributions by Allied Health Technicians, i.e. Dental Assistants and Medical Device Technicians are critical in reducing clinical risks. Dental assistants are the main custodians of infection control and sterilization and medical device technicians are the ones who take care of the operational fidelity and calibration of life critical technologies. Objective: The objectives of the proposed systematic review are to assess how Allied Health technicians can be used to improve patient safety in Saudi Arabian healthcare environments. Methods: Based on PRISMA 2020, a systematic search was performed in PubMed, the Saudi Digital Library (SDL), ScienceDirect, and Scopus within the year 2015 and 2026 to identify peer-reviewed articles. Search involved Boolean strings which were a combination of terms such as Allied Health, Dental Assistant, Medical device technician and patient safety plus Saudi Arabia. The selection of studies was performed according to predetermined inclusion criteria, including empirical information of KSA-based healthcare facilities. Conclusion: The analysis of the review shows that Allied Health Technicians are crucial foundations of the Saudi safety system, and CBAHI accreditation is one of the main factors that should trigger protocols compliance. Technical competency that is high in sterilization and device maintenance has major gaps in the area of "Safety Culture" particularly in the reporting of errors that is non-punitive. The research concludes that technicians can play an important role in mitigating both technical and biological hazards; however, the primary challenge of the Saudi healthcare system is to adopt standardized national certifications and shift to a Just Culture, which will enable these professionals to be the most powerful leaders in terms of safety..